Interface instabilities in hydrodynamic relativistic jets - Abolmasov, Pavel; Bromberg, Omer (Monthly notices of the Royal Astronomical Society, 2023)
ABSTRACT Both the dynamics and the observational properties of relativistic jets are determined by their interaction with the ambient medium. A crucial role is played by the contact discontinuity at the jet boundary, which in the presence of jet collimation may become subject to Rayleigh–Taylor instability (RTI) and Richtmyer–Meshkov instability (RMI). Here, we study the evolution of these instabilities in non-magnetized relativistic jets using special relativistic three-dimensional hydrodynamic simulations. We show that the growth of initial perturbations is consistent with relativistic RTI operating in the jet collimation region. The contribution of RMI becomes important downstream from the collimation shock in agreement with the theoretical expectations. Both instabilities reach non-linear scales above the shock convergence point and trigger strong turbulence, mixing the jet with the ambient matter. We devise an analytic solution for the mixing rate and show that it is sensitive to the external density gradients. Our results may be applied to different types of astrophysical objects. In particular, different contribution of interface instabilities is a natural explanation for the observed dichotomy between FR-I and FR-II radiogalaxies. The rapid slow-down in the jet of M87 is consistent with baryon entrainment from the circumnuclear matter with the observed density distribution. In microquasars, baryon loading triggered by interface instabilities is a probable reason for the low observed Lorentz factors. We show that the observed variability in gamma-ray bursts cannot come from mixing driven by interface instabilities and likely originates from the engine, suggesting the presence of magnetic fields in the jet.